PENATALAKSANAAN FISIOTERAPI PADA KASUS PASCA REKONTRUKSI MEDIAL PATELLOFEMORAL LIGAMENT SINISTRA DI KLINIK BINTANG PHYSIO BANDUNG: CASE REPORT - Nurul Azizah; Wahyu Tri Sudaryanto; Monalisa Meidania (Bajang Institute, 2023)
Background: Medial Patellofemoral Ligament (MPFL) is the main ligament that provides 60% defense against patella dislocation. MPFL reconstruction is one of several operative treatment approaches available to treat patellar instability, which is characterized by acute or recurrent patella dislocation, reduced functional activity, and decreased exercise activity. Objective: to determine the physiotherapy management using cryotherapy, electrotherapy, and exercise therapy methods in cases of post-reconstruction of the medial patellafemoral ligament. Methods: a study using the Case Report method conducted at the Bintang Physio Bandung Clinic in male patients aged 26 years, diagnosed with post-reconstructive physiotherapy of the Medial Patellafemoral Ligament. Results: there was a decrease in the level of pain, there was an increase in anthropometric measurements of the circumference of the upper and lower leg segments, which meant that there was an increase in quadriceps and hamstring muscle tone, an increase in the range of motion of the joints, an increase in the MMT value. Conclusion: based on research using case reports, it shows that physiotherapy management with the evaluation results obtained has increased.